Knowledge attitude and behavior practices regarding clinical presentation, transmission, preventive measures and management of malaria and dengue among the health care personnel - Dudi, Jitendra Kumar; Dogne, Chandragopal; Afrin, Sana; Singh, Abhay; Raghunath, Deepa; S. B., Bansal; Dixit, Shivam; Narendranath, R. (International Journal of Research in Medical Sciences, 2022)
Background: According to WHO, in 2020, there were an estimated 241 million cases of malaria worldwide. The estimated number of malaria deaths stood at 627000 in 2020. Similarly, the global incidence of dengue has grown dramatically with about half of the world’s population now at risk. The present study is an attempt to assess the knowledge attitude and behaviour practices regarding clinical presentation, transmission, preventive measures and management of malaria and dengue among the health care personnel (HCPs). Methods: The present cross-sectional study was carried out in the department of community medicine, MGM medical college Indore. Among one tribal (Barwani) and one non-tribal district of Indore, participant selection was done by simple random sampling technique using chit method of all districts covered under Indore division. The ethical clearance was obtained from our institute ethical committee. Results: The advice given by all the HCPs for the prevention of malaria infection is eradication of breeding site of mosquito by preventing water stagnation. The 75% ANMs, 90% lab technicians, 100% MOs, malaria inspectors and MPWs were aware of the time of the bite of female anopheles’ mosquito. Majority of the HCPs were aware of the time of the bite of female Aedes mosquito, the warning signs dengue infection and were of the opinion that they give advice of keeping drinking water containers (Cisterns, tanks) tight closed. Conclusions: All the HCPs were aware of the prominent symptoms of malaria and promoted actively the integrated vector control measures in their allocated areas of work.